(untitled) (Research, Society and Development, 2021)
Soy is a crop of great expressiveness worldwide and Brazil is currently the largest producer and exporter of this crop, with territorial potential for expansion of its cultivation. In view of the forecasts made by the main governmental institutions (climate change, population increase, and the scarcity of water resources), ensuring food security for a growing population will require strategies and improvements aimed at increasing productivity. The objective was to identify attributes of the environment and soybean plants that make them tolerant to water deficit and enable increased production in semi-arid environments in northeastern Brazil. Given that most of the major soy producing countries are composed mostly of arid and semi-arid territories, and due to the current climate changes, there is a strong tendency that new areas may be becoming arid and semi-arid. The solutions to cope with the water deficit stress imposed on soybean in arid and semi-arid environments need to be related to physiological, morphological and genetic improvements to help cope with this stress. Root enlargement, increased efficiency in nitrogen fixation, control of stomatal conductance and the efficient use of water by the plant are some of the challenges that genetic engineering will have to address in order to develop a water deficit tolerant soybean variety. More studies that aim to find answers capable of solving the water deficit in soybean should be conducted.